Less elephant slaughter in the Okapi Faunal Reserve, Democratic Republic of Congo, with Operation Tango - Mubalama, Leonard; Mapilanga, Jean (Pachyderm, 2001)
Reviews the apparent success of Operation Tango, a military-wildlife guard anti-poaching initiative, devised in October 2000 in an attempt to eliminate elephant and bushmeat poaching and illegal coltan mining in Okapi Faunal Reserve in eastern Democratic Republic of Congo. Large scale poaching activities were evident, with 17 new or recent poaching camps reported. 20 poachers were caught with evidence (111 kg raw ivory and 215 kg elephant meat). 17 weapons (small machine guns) and 331 rounds of ammunition were confiscated by a 34 man team of Uganda People’s Defense Forces (UPDF) and Armee Populaire Congolaise (APC) personnel. All active law enforcement was vested in a closely supervised rapid deployment strike force based at Epulu. The force undertook armed patrols throughout the Reserve, manned observation at strategic vantage points, and responded to intelligence reports or calls for assistance from the outposts. 3 months prior to the launch of Operation Tango less than 10% of the Reserve was under wildlife management authority control. After 5 months of the Operation no new signs of poaching were found. Future management needs/objectives are discuss.